PERAN MAHASISWA KKN UNIVERSITAS NEGERI PADANG DALAM MENGHIDUPKAN SEMANGAT HIJRAH: LOMBA 1 MUHARAM SEBAGAI WADAH PEMBENTUKAN KARAKTER ISLAMI DI MASYARAKAT NAGARI BATU KALANG UTARA KEC. PADANG SAGO KABUPATEN PADANG PARIAMAN - aslimeri; Cahaya Adha; Kayla Nur Azizah; Puti Nur Annisya; Putri Melinda Hasibuan; Vicesa Padusianjoci (Jurnal IKEOR, 2025)
The Community Service Program (KKN) of Universitas Negeri Padang (UNP) in Nagari Batu Kalang Utara, Padang Sago District, Padang Pariaman Regency, involved 20 students from various faculties. This program carried the theme: "Reviving the Spirit of Hijrah: 1 Muharram Competitions as a Platform for Islamic Character Building in the Community." This article discusses the implementation of additional KKN student activities in the fields of education, health, and community engagement. The main focus was on organizing Islamic-themed competitions at the korong (village subunit) level to commemorate 1 Muharram, including tilawah (Qur’an recitation), tahfidz (memorization), adzan (call to prayer), kultum (short sermon), nasheed (Islamic songs), and Islamic quiz competitions. Students were actively involved in every stage, from planning and execution to mentoring the participants. The results showed high community enthusiasm and a noticeable increase in religious spirit and Islamic character development among children and adolescents. These activities also strengthened collaboration between students and the local community and encouraged the practical application of academic knowledge in real-life social contexts. It is hoped that similar programs can be sustained and serve as a model for impactful community service.